Photovoltaic Testing for Energy Yield Predictions with Sensitivity to Spectral Shifts - Looney, Erin E.; Liu, Zhe; Classen, Andrej; Buonassisi, Tonio; Peters, Ian Marius (Conference Record of the IEEE Photovoltaic Specialists Conference, 2020)
Solar spectra change depending on location, weather, and time of day around the world. These spectral variations affect the performance of photovoltaic (PV) cells and modules and are not captured by standard testing procedures. We introduce a method to classify spectra and use this classification to develop a testing procedure to reproduce spectral conditions of locations within various climate zones. With LED solar simulators becoming commercially available and representative sets of outdoor spectra found, the gap between real world outdoor testing and indoor testing is closing. With LED-based testing of CdTe, Si, and GaAs PV cells, we show that the effects of spectral shifts on short circuit current are captured, demonstrating the potential use of this method for more accurate testing of solar modules indoors.
CRIS-Team Scopus Importer:2022-06-05
Keywords: LED solar simulators; solar spectrum; testing standards